Experimental Approach: FTIR and 1HNMR Based Metabolic Fingerprinting Detect Drugs Interactions with Physiological Pathways of Incubated Edible Plants in Acidic Medium - Abdelkader, Amal F.; Aldughaish, Adnan M.; Al-hanout, Fatemah K. (Asian Journal of Biological and Life Sciences)
The objective of the present study was investigating impacts of popular drugs on the metabolic fingerprinting of two edible plants, D. carota root and P. sativum leaves under synthetic stomach conditions regarding temperature and pH. Spectral analyses of fourier transform infrared (FTIR) and nuclear magnetic resonance (1HNMR) of incubated plants with 1/24 part of each tablet in water "pH 5" showed pathways fluctuation within 90 minutes. FTIR spectra of incubated plants in the painkiller, hypersensitive and the drugs mixture showed fatty acids overall shifted spectra. The hypersensitive had influenced the saccharides, polypeptides and proteins. Calcium, vitamins and the painkiller induced polypeptides, proteins and saccharides variations. The 1HNMR spectra of incubated plants with the hypersensitive have detected disappearance of total sixteen metabolites, and the appearance of eleven ones in both plants. The 1HNMR spectra of painkiller plants have detected eighteen metabolic absence and twelve new appearance of metabolites. We hypothesize the possible potential role of drugs in reacting with vegetables physiological pathways in the human stomach, starting with forming new complexes and ending with shifting the metabolic fingerprinting of plants. However, the subsequent impact of these originated complexes on human health with the accumulated practice of eating vegetables together with medicine requires further studies.
Keywords: 1H NMR; Daucus carota; Drugs; Fourier transform infrared; FTIR; Nuclear resonance of the proton; Petroselinum sativum